Strategi Digital Marketing melalui Aplikasi Tiktok dalam Meningkatkan Brand Awareness Produk : Pengabdian - Muhammad Fikri Setiawan; Muamar (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Digital marketing has now become a key strategy for increasing product brand awareness, especially for micro, small, and medium enterprises (MSMEs). TikTok, as a short video-based platform with a content distribution algorithm focused on audience engagement, provides new opportunities for MSMEs to reach consumers widely at a relatively low cost. This study aims to analyze effective digital marketing strategies through TikTok in increasing MSME product brand awareness. The method used is descriptive qualitative with a literature study approach and case simulations on local MSMEs. The results show that the use of storytelling strategies, the use of music and trending hashtags, collaboration with influencers, and upload consistency are proven to increase brand visibility and interaction with consumers. This research is expected to provide theoretical and practical contributions in strengthening TikTok's role as a digital promotional medium for MSMEs in the creative economy era.